Effect of repair methods and materials on the flexural strength of 3D-printed denture base resin - do Carmo Viotto, Hamile Emanuella [UNESP]; Silva, Marcela Dantas Dias [UNESP]; Nunes, Thaís Soares Bezerra Santos [UNESP]; Coelho, Sabrina Romão Gonçalves [UNESP]; Pero, Ana Carolina [UNESP] (XMLink, 2022)
PURPOSE. The aim of this study was to evaluate the flexural strength of a 3D-printed denture base resin (Cosmos Denture), after different immediate repair techniques with surface treatments and thermocycling. MATERIALS AND METHODS. Rectangular 3D-printed denture base resin (Cosmos Denture) specimens (N = 130) were thermocycled (5,000 cycles, 5°C and 55°C) before and after the different repair techniques (n = 10 per group) using an autopolymerized acrylic resin (Jet, J) or a hard relining resin (Soft Confort, SC), and different surface treatments: Jet resin monomer for 180 s (MMA), blasting with aluminum oxide (JAT) or erbium: yttrium-aluminum-garnet laser (L). The control group were intact specimens. A three-point flexural strength test was performed, and data (MPa) were analyzed by ANOVA and Games-Howell post hoc test (α = 0.05). Each failure was observed and classified through stereomicroscope images and the surface treatments were viewed by scanning electron microscope (SEM). RESULTS. Control group showed the highest mean of flexural strength, statistically different from the other groups (P <.001), followed by MMA+J group. The groups with L treatment were statistically similar to the MMA groups (P >.05). The JAT+J group was better than the SC and JAT+SC groups (P <.05), but similar to the other groups (P >.05). Adhesive failures were most observed in JAT groups, especially when repaired with SC. The SEM images showed surface changes for all treatments, except JAT alone. CONCLUSION. Denture bases fabricated with 3D-printed resin should be preferably repaired with MMA+J. SC and JAT+SC showed the worst results. Blasting impaired the adhesion of the SC resin.
Keywords: Dental prosthesis; Denture bases; Flexural strength; Printing; Resins; Three-dimensional